2006
DOI: 10.1373/clinchem.2005.058776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample Collection Tubes on Cerebrospinal Fluid Concentrations of Tau Proteins and Amyloid β Peptides

Abstract: the oral administration of metallic colloids, in particular colloidal silver protein, has been reported to have toxic effects (2 ). Despite this, dozens of companies sell metal colloids as nutritional supplements.Many metal colloids have been rebranded as "nano" compounds to further intensify the public's interest in their utility. Although clinical concern about the use of colloidal metallic compounds is longstanding, their effects on laboratory tests have not been investigated. These particles are of particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 12 publications
11
92
0
4
Order By: Relevance
“…Although polypropylene (PP) was previously reported as the best material for CSF collection tubes (2 ), heterogeneity in CSF A␤1-42 values was observed with different PP sampling tubes (3 ). Because the recommendation to use PP tubes did not lead to standardization of clinical cutoff values (4 ), we decided to fully address this issue by comparing various types of tubes within an actual clinical work flow and by analyzing the material of different commercially available PP tubes.…”
mentioning
confidence: 99%
“…Although polypropylene (PP) was previously reported as the best material for CSF collection tubes (2 ), heterogeneity in CSF A␤1-42 values was observed with different PP sampling tubes (3 ). Because the recommendation to use PP tubes did not lead to standardization of clinical cutoff values (4 ), we decided to fully address this issue by comparing various types of tubes within an actual clinical work flow and by analyzing the material of different commercially available PP tubes.…”
mentioning
confidence: 99%
“…Polystyrene and polyethylene tubes have been shown to artefactually diminish CSF levels of amyloid beta compared with polypropylene tubes, through adsorption of the protein to the plastic surface [77]. Similar effects may well be seen with any other protein; most have not been investigated for such technical effects.…”
Section: Protein Markers Of Neuronal Deathmentioning
confidence: 99%
“…Composition of tubes used to collect CSF during lumbar puncture has a strong influence on Aβ peptide concentrations [32]. This is in relation with the tendency of Aβ peptides to adsorb to the walls of the tube.…”
Section: Csf Collection Tubesmentioning
confidence: 99%
“…Hence, it has been shown that glass and polystyrene tubes led to lower measured concentrations of Aβ peptides [25,31]. Polypropylene tubes were believed to reduce this phenomenon [32]. However, even polypropylene tubes which are not made entirely of polypropylene, and have various surface treatments, have a major impact on Aβ peptide measured concentrations [25].…”
Section: Csf Collection Tubesmentioning
confidence: 99%